Use of a sensitive multisugar test for measuring segmental intestinal permeability in critically ill, mechanically ventilated adults: A pilot study. Issue 2 (30th April 2021) - Tatucu‐Babet, Oana A.; Forsyth, Adrienne; Udy, Andrew; Radcliffe, Jessica; Benheim, Devin; Calkin, Caroline; Ridley, Emma J.; Gantner, Dashiell; Jois, Markandeya; Itsiopoulos, Catherine; Tierney, Audrey C.
Abstract: Background: Increased intestinal permeability (IP) is associated with sepsis in the intensive care unit (ICU). This study aimed to pilot a sensitive multisugar test to measure IP in the nonfasted state. Methods: Critically ill, mechanically ventilated adults were recruited from 2 ICUs in Australia. Measurements were completed within 3 days of admission using a multisugar test measuring gastroduodenal (sucrose recovery), small‐bowel (lactulose‐rhamnose [L‐R] and lactulose‐mannitol [L‐M] ratios), and whole‐gut permeability (sucralose‐erythritol ratio) in 24‐hour urine samples. Urinary sugar concentrations were compared at baseline and after sugar ingestion, and IP sugar recoveries and ratios were explored in relation to known confounders, including renal function. Results: Twenty‐one critically ill patients (12 males; median, 57 years) participated. Group median concentrations of all sugars were higher following sugar administration; however, sucrose and mannitol increases were not statistically significant. Within individual patients, sucrose and mannitol concentrations were higher in baseline than after sugar ingestion in 9 (43%) and 4 (19%) patients, respectively. Patients with impaired (n = 9) vs normal (n = 12) renal function had a higher L‐R ratio (median, 0.130 vs 0.047; P = .003), lower rhamnose recovery (median, 15% vs 24%; P = .007), and no difference in lactulose recovery. Conclusion: Small‐bowel and whole‐gut permeability measurements are possible to complete in the nonfasted state, whereas gastroduodenal permeability could not be measured reliably. For small‐bowel IP measurements, the L‐R ratio is preferred over the L‐M ratio. Alterations in renal function may reduce the reliability of the multisugar IP test, warranting further exploration.